2021
DOI: 10.1159/000517504
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Self-Help Plus in Preventing Mental Disorders in Refugees and Asylum Seekers in Western Europe: A Multinational Randomized Controlled Trial

Abstract: <b><i>Introduction:</i></b> Self-Help Plus (SH+) is a group-based psychological intervention developed by the World Health Organization for managing stress. <b><i>Objective:</i></b> To assess the effectiveness of SH+ in preventing mental disorders in refugees and asylum seekers in Western Europe. <b><i>Methods:</i></b> We conducted a randomized controlled trial in 5 European countries. Refugees and asylum seekers with psychological distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 47 publications
5
75
0
1
Order By: Relevance
“…Our target population was composed of workers from NCH with higher educational levels and with lower levels of symptoms at baseline, so that the effect of a low-intensity intervention might be less emphasized. On the other hand, our results appear to be relatively more aligned with those of a recent RCT testing the standard SH+ intervention in Europe with a preventative aim [ 63 ]. In this trial, 459 asylum seekers and refugees, resettled in five European countries, with increased psychological distress but without a formal psychiatric diagnosis, were randomized to receive the SH+ or enhanced usual care (i.e.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our target population was composed of workers from NCH with higher educational levels and with lower levels of symptoms at baseline, so that the effect of a low-intensity intervention might be less emphasized. On the other hand, our results appear to be relatively more aligned with those of a recent RCT testing the standard SH+ intervention in Europe with a preventative aim [ 63 ]. In this trial, 459 asylum seekers and refugees, resettled in five European countries, with increased psychological distress but without a formal psychiatric diagnosis, were randomized to receive the SH+ or enhanced usual care (i.e.…”
Section: Discussionsupporting
confidence: 81%
“…However, the authors did report, as a secondary result, a positive effect for psychological distress, depressive symptoms, perceived problems and well-being at post-intervention. For well-being (as measured with the WHO-5, like in our study), the estimate was still significant at the six-month follow-up [63].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The best health infrastructure and the largest mental health care resources are of no value if affected populations are stigmatized or if no knowledge exists regarding diseases or treatment options on the caretakers' side. Equally important, health literacy needs to be present on the caregivers' side with respect to cultural differences in idioms of distress or concerning culture-sensitive treatment modifications (10,11). (12,13).…”
Section: Challenge 3: Public Trust and Health Literacymentioning
confidence: 99%
“…Recently, two large RCTs evaluated a new psychological intervention called Self-Help Plus (SH+) and developed by the WHO, with the aim of preventing the onset of mental disorders in asylum seekers and refugees. These trials identified a beneficial effect of SH+ in preventing the frequency of mental disorders at post-intervention (Purgato et al ., 2021 ) and at 6-month follow-up (Acarturk et al ., in press ).…”
Section: Effectiveness Trials On Mental Health and Psychosocial Support Interventions: The Current Paradigmmentioning
confidence: 99%